Gim Edukasi Bernarasi Cerita untuk Edukasi Prasekolah Normal Baru: Studi Kasus di TK Lintang, Surabaya - Pratama Wirya Atmaja; Sugiarto Wirya Sugiarto; Diana Aqidatun Nisa (Computer Engineering Departement, Universitas Komputer Indonesia, 2022)
Educational games are a state-of-the-art method for education in the 21st century. However, they have not been applied for new-normal education in preschools. To contribute to the matter, we developed an educational game to help TK Lintang, a preschool institution in Surabaya, conduct